(3GdEOGQI GdafObjI h GdSjGMjI (B/s - (3MGaX, YHO GdcQjes ((3YeGf(B: s (3OGQ GSGeI(B, s, 2009)
(3eGgjI EOGQI GdafGOb , GdMGShH GdBdj aj UfGYI GdafGOb , fXGe GdeYdheGJ GdGOGQjI GdafObjI , GdGbSGe GdJTZjdHI aj GdafOb (B: (3bSe GdecJH GdGeGej ,GdJShjb h GdJQhjL h GdGYdGf GdafObj , bSe GdeWGYe h GdGZPjI h GdeTQhHGJ , bSe GdMadGJ h GdefGSHGJ h GdeDJeQGJ , GdGbSGe GdeSGfOI aj GdafOb (B: (3bSe GOGQI TDhf GdehXajf aj GdafGOb , bSe GdJOHjQGdafObj , bSe GdeTJQjGJ h GdeNGRf ,bSe GdeMGSHHI GdeGdjI h bSe GdSdGeI h GdGef GdafObj eY OQGSI GdGOGQI GdSjGMjI HGdJWQb Gdi eJgjI GdSjGMI h GdVjGaI , GdLhOI aj GdSjGMI h GdSjGMI GdUMjI h GdYdGLjI (B.s
(3eQGLY U(B.275s
Keywords: (3GdGOGQIs; (3GdSjGMIs; (3GdafGObs